Relationship between sociodemographics, dietary intake and physical activity with gestational weight gain among pregnant women in Rafsanjan City, Iran - Ebrahim, Fatemeh; Mohd Shariff, Zalilah; Tabatabaei, Seyed Zia; Fathollahi, Mahmood Sheikh; Mun, Chan Yoke; Nazari, Mozhgan (International Centre for Diarrhoeal Disease Research Bangladesh, 2015)
Gestational weight gain (GWG) is a determinant of health and nutrition of mothers and offspring. However, many factors associated with GWG are not completely understood. The present study assessed the relationship between sociodemographics, dietary intake, and physical activity with GWG in 308 Iranian pregnant women attending government healthcare centres in Rafsanjan city, Iran. Women gained an average of 12.87±3.57 kg during pregnancy while 54% did not gain weight within the Institute of Medicine (IOM)-recommended range. Univariate logistic models showed that gestaional weight gain was related to age, pre-pregnancy body mass index (BMI), energy intake, and sitting time. Cumulative logit model showed positive relationship between age (p=0.0137) and pre-pregnancy BMI (p<0.0001) with GWG. All pregnant women should be counselled on achieving the reccomended GWG to prevent adverse maternal and prenatal outcomes. Pre-pregnancy and gestational nutritional status and physical activity should be emphasized in antenatal care.